2023
DOI: 10.1039/d3nr02452k
|View full text |Cite|
|
Sign up to set email alerts
|

Ion and water adsorption to graphene and graphene oxide surfaces

Abstract: Understanding molecular-scale information about water and ion interactions at graphene and graphene oxide surfaces is critical for successful application development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 116 publications
(198 reference statements)
0
8
0
Order By: Relevance
“…The highest value of differential adsorption (d E ads /d N i ) is in good agreement with the experimental data (Figure a). Computational simulation and experimental data revealed that the water molecules can form stable hydrated multilayers on the flat units of graphene . The highest peak observed at an adsorption energy of −2.15 kcal mol –1 (Figure ) indicates a large number of water molecules adsorbed on the surface of the BT-GR composite.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The highest value of differential adsorption (d E ads /d N i ) is in good agreement with the experimental data (Figure a). Computational simulation and experimental data revealed that the water molecules can form stable hydrated multilayers on the flat units of graphene . The highest peak observed at an adsorption energy of −2.15 kcal mol –1 (Figure ) indicates a large number of water molecules adsorbed on the surface of the BT-GR composite.…”
Section: Resultsmentioning
confidence: 98%
“…However, the highest values of E ads for BT-NT, BT-NH, and BT-FU (Figure b) are the subject of controversy regarding the mode of adsorption of water molecules. The increased value of E ads can be explained by the impact of possible adsorption of a part of water molecules in the internal channel of nanotubes, nanohorns, and fullerene. It is known that the carbon nanotube channel is strongly hydrophobic but can filled up with water molecules forming a hydrogen-bonded chain . The structure of carbon nanohorns has a closed horn tip at one side and an open end on the other side, allowing the water molecules to enter .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It specifically discusses model interfacial systems that allow direct molecular-scale measurements. For a broader understanding, readers are encouraged to refer to comprehensive reviews on LLE. , Recent reviews also cover interfaces in other separation systems, such as graphene-based materials …”
Section: Introductionmentioning
confidence: 99%
“…3,4 Recent reviews also cover interfaces in other separation systems, such as graphene-based materials. 5 The demand for heavy elements is steadily increasing due to their utilization in energy production, vehicles, magnets, electronic displays, and other strategic technologies. Surprisingly, these ions have received little attention in interfacial studies, resulting in limited experimental and theoretical knowledge about multivalent and complex ions at interfaces, most of which has been developed in the past decade.…”
Section: ■ Introductionmentioning
confidence: 99%